Implementasi Putusan Mahkamah Arbitrase Internasional Dan Akibat Hukumnya: Konflik Antara China dan Filipina Atas Laut China Selatan - Toisuta, Muhamad Rizky; Peilouw, Johanis Stenly Franco; Daties, Dyah Ridhul Airin (PATTIMURA Law Study Review, 2025)
The South China Sea dispute stems from China's historical "nine-dash line" claim to almost the entire area, which the Philippines rejects. In 2013, the Philippines brought the dispute to the Permanent Court of Arbitration (PCA). The PCA's July 12, 2016 ruling affirmed that China's claim had no legal basis under UNCLOS 1982 and rejected the validity of the "nine-dash line", while designating areas such as Scarborough Shoal as part of the Philippines' Exclusive Economic Zone (EEZ). China's stance in rejecting the arbitral award has also been criticized by surrounding countries and the international community, who consider such actions to threaten regional security and raise concerns about the potential for armed conflict in the strategic region. The author uses normative juridical research. In general, normative legal research is research that focuses on legal issues in a particular jurisdiction. Normative legal research focuses on the statutory approach, which leads to the idea that normative research is research on laws and regulations. The analysis focuses on the provisions of UNCLOS 1982, international dispute resolution mechanisms, and the implementation of arbitral awards in global legal practice. The implementation of the Permanent Court of Arbitration (PCA) award faces significant political challenges due to China's rejection, so the legal consequences are more political and economic than formal juridical. The Philippines respects and seeks to implement the award, while China expressly rejects it. This rejection has led to various legal consequences, including the application of enforcement mechanisms that include economic sanctions, membership sanctions in international organizations, and unilateral sanctions from certain countries. Although the PCA ruling has the binding force of international law, China's non-compliance with the ruling shows the limitations of international law enforcement mechanisms in maritime disputes involving major powers. Therefore, resolving South China Sea disputes requires a more comprehensive approach, combining legal, political and diplomatic aspects to achieve sustainable regional stability. The role of the international community and relevant countries is crucial in encouraging compliance with international law and preventing conflict escalation that can have far-reaching regional and global impacts.